1971
DOI: 10.1192/bjp.119.551.435
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Lithium vs. Chlorpromazine in Acute Schizophrenics

Abstract: A previous double-blind controlled evaluation of lithium and chlorpromazine in both manic and schizo-affective individuals carried out in this unit (Johnsonet al., 1968) indicated that 85 per cent of the schizo-affectives showed a worsening of thought disorder when treated with lithium carbonate, the majority developing symptoms of an acute brain syndrome. The possibility of experimental design accounting for such treatment outcome must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

1972
1972
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 14 publications
0
28
1
Order By: Relevance
“…In contrast to the high rates of lithium-induced toxic-confusional states reported by Johnson et al [1968] and Shopsin et al [1971] (i.e., 71 and 54%, respectively), other investigators (see table I) have reported rates of lithium-induced toxic-confusional states in schizophrenic patients of 30% or below [West and Meitzer, 1979;Prien et al, 1972;Small et al, 1975]; six studies have reported rates of 0% [Zall et al, 1968;Angst et al, 1969;Alexander et al, 1977;Biederman et al, 1979;Growe et al, 1979;Carmen et al, 1981]. Also contrary to Johnson et al [1968] and Shopsin et al [1971] who reported that lithium produced a worsening of psychomotor excite ment, delusions and hallucinations, a number of investigators have re ported clinical improvements in lithium-treated schizophrenic patients [Zall et al, 1968;Prien et al, 1972;Growe et al, 1979;Angst et al, 1969Angst et al, , 1970Small et al, 1975;Alexander, 1979;Biederman et al 1979;Carmen et al, 1981].…”
Section: Acutecontrasting
confidence: 48%
See 2 more Smart Citations
“…In contrast to the high rates of lithium-induced toxic-confusional states reported by Johnson et al [1968] and Shopsin et al [1971] (i.e., 71 and 54%, respectively), other investigators (see table I) have reported rates of lithium-induced toxic-confusional states in schizophrenic patients of 30% or below [West and Meitzer, 1979;Prien et al, 1972;Small et al, 1975]; six studies have reported rates of 0% [Zall et al, 1968;Angst et al, 1969;Alexander et al, 1977;Biederman et al, 1979;Growe et al, 1979;Carmen et al, 1981]. Also contrary to Johnson et al [1968] and Shopsin et al [1971] who reported that lithium produced a worsening of psychomotor excite ment, delusions and hallucinations, a number of investigators have re ported clinical improvements in lithium-treated schizophrenic patients [Zall et al, 1968;Prien et al, 1972;Growe et al, 1979;Angst et al, 1969Angst et al, , 1970Small et al, 1975;Alexander, 1979;Biederman et al 1979;Carmen et al, 1981].…”
Section: Acutecontrasting
confidence: 48%
“…Shopsin et al [1971] soon afterwards reported a similarly high rate (54% of cases) of severe lithium neurotoxicity in another sample of schizophrenic patients representing a variety of subtypes of schizophrenia. These reports led to the hypothesis that schizo phrenics have a lower threshold for the neurotoxic effects of lithium.…”
Section: Acutementioning
confidence: 99%
See 1 more Smart Citation
“…High dose amphetamine may cause hyperactivity via release of dopamine and a mechanism not inhibitable by lithium at therapeutic doses [Taylor and Snyder, 1971;Thornburg and Moore, 1973;Reches et al, 1978]. A clinical parallel may be the ability of Li to calm manic excitement with little benefit for the excitement of schizophrenia [Shopsin et al, 1971], Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Shopsin et al (1971) conducted a controlled study with 21 acute schizophrenic patients, treated with either lithium or chlorpromazine. They found that lithium had no effect in schizophrenic symptoms, and some of the schizophrenic patients got worse, developing symptoms of a "toxic-confusional state."…”
Section: Schizophreniamentioning
confidence: 99%